Perlindungan Hak Anak dalam Hukum Keluarga Islam: Studi Komparatif Antara Hukum Islam dan Hukum Nasional - Sugeng Aminudin; Abdurrahman Hakim; Muhammad Thoriq (Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
This article aims to analyze and compare the protection of children's rights in Islamic family law with Indonesian national law. The main focus of this study is to identify the similarities and differences in the approach to child rights protection between the two legal systems, as well as to evaluate their effectiveness in ensuring the best interests of children. This study uses a qualitative method with a comparative study approach, through the analysis of legal documents, jurisprudence, and related literature. Data were collected from primary and secondary sources, including the Qur'an, Hadith, the Child Protection Law, and other national regulations. The academic debates raised in this article include discussions on whether Islamic law is more proactive in protecting children’s rights than national law, especially in relation to issues of custody, maintenance, and education. Some academics argue that Islamic law has a strong moral basis in protecting children’s rights, while others emphasize that national law is more relevant to modern social developments and international conventions such as the Convention on the Rights of the Child. The results of this study indicate that both legal systems, both Islamic law and national law, have a strong commitment to protecting children's rights, although with different approaches. Islamic law tends to be more normative and based on religious values, while national law is more legalistic and integrated with international standards. In the Indonesian context, the combination of these two systems offers comprehensive protection of children's rights in family law.